Gd(III)‐DO3A‐SBMPP:An Effort to Develop the MRI Contrast Agent with Enhanced Relaxivity. Issue 19 (17th November 2016) - Rangaswamy, Sandhya; Varshney, Raunak; Tiwari, Anjani K.; Sethi, Swarndeep K.; Hemanth kumar, B. S.; Ojha, Himanshu; Sandeep Kaur‐Ghumaan,; Mishra, Anil K.
Abstract: Rational design of a new class of MR (magnetic resonance) contrast agent for enhance relaxivity has been described. The click chemistry was employed to incorporate two moieties of 1‐(2‐methoxyphenyl)piperazine and serinol as a linker to enhance the affinity at the recognition sites. The designed ligand was attached to DO3A to synthesize DO3A‐serinol‐bis‐MPP (SBMPP) in 89 % yield. Gd‐DO3A‐SBMPP showed enhanced relaxivity r1 of 10.85±0.04 mM −1 s −1 as compare to known gadolinium based contrast agents in clinics. The potentiometric titration of gadolinium loaded SBMPP exhibited strong selectivity for Gd 3+ over physiological metal ions such as Zn 2+ and Cu 2+ . Thus, the synthesis of bis‐conjugate could be observed as novel, instructive and initial proof of concept for the synthesis of MR contrast agent with enhanced relaxivity. The preliminary findings show the good biocompatibility and potential functionalities of MPP analogue to target brain regions through MRI. Abstract : A novel bivalent methoxyphenylpiperazine‐serinol based MR contrast agent has been develop by utilizing the click chemistry approach. The bivalent ligands display better binding at the receptor site, as single entity is capable of binding simultaneously to their target via two pharmacophore. The synthezised DO3A‐Serinol‐bis‐MPP showed enhance relaxivity.